Pathomorphological features of eyelid tissue scarring after treatment with platelet-rich plasma - I. A. Filatova; Yu. A. Pavlenko; N. S. Izmailova; A. A. Zharov; S. A. Shemetov; I. N. Ponomarev; N. V. Borovkova (Российский офтальмологический журнал)
Purpose: to evaluate the effectiveness of anti-scar treatment of eyelid tissues with platelet-rich plasma (PRP) lysate by pathomorphological examination. Material and methods. 20 patients (men aged 27–64 years with eyelid scars caused by traumatic tissue rupture) underwent reconstructive plastic surgery on their eyelids. All patients had similar injuries and traumatic agents, the type and localization of the scar, and the same duration of the post-traumatic period (12 months after the injury). The patients were divided into 2 groups depending on the application of anti-scar treatment using PRP lysate in the preoperative period. The treatment consisted in injecting a personalized biotransplant into the scar tissue. During the surgery, a fragment of scar tissue was taken from each patient for pathomorphological examination. Results. In the control group, the pathomorphological picture was of the same type and corresponded to the third phase of wound healing with remodeling and the formation of a rough scar. The third phase of wound healing with scar remodeling in patients of the main group was characterized by significantly less pronounced fibrotic-dystrophic changes in both cellular and stromal components of the dermis and hypodermis. Conclusion. In the main group with PRP lysate therapy, scar tissue was characterized by significantly less pronounced fibrotic-dystrophic changes in both cellular and stromal components of the dermis and hypodermis as compared to the control group. The observed morphological picture was close to a complete involution of the scar with its restructuring, approaching the normal histoarchitectonics of the dermis and hypodermis.